Effects of silver impurity on the structural, electrical, and optical properties of ZnO nanowires - Kim Sangsig; Lee Sang; Kim Kyoungwon; Debnath Pulak; Lee Deuk-Hee (Nanoscale Research Letters, 2011)
Abstract 1, 3, and 5 wt.% silver-doped ZnO (SZO) nanowires (NWs) are grown by hot-walled pulsed laser deposition. After silver-doping process, SZO NWs show some change behaviors, including structural, electrical, and optical properties. In case of structural property, the primary growth plane of SZO NWs is switched from (002) to (103) plane, and the electrical properties of SZO NWs are variously measured to be about 4.26 × 106, 1.34 × 106, and 3.04 × 105 Ω for 1, 3, and 5 SZO NWs, respectively. In other words, the electrical properties of SZO NWs depend on different Ag ratios resulting in controlling the carrier concentration. Finally, the optical properties of SZO NWs are investigated to confirm p-type semiconductor by observing the exciton bound to a neutral acceptor (A0X). Also, Ag presence in ZnO NWs is directly detected by both X-ray photoelectron spectroscopy and energy dispersive spectroscopy. These results imply that Ag doping facilitates the possibility of changing the properties in ZnO NWs by the atomic substitution of Ag with Zn in the lattice.